2017
DOI: 10.3892/mmr.2017.7455
|View full text |Cite
|
Sign up to set email alerts
|

PHD3 affects gastric cancer progression by negatively regulating HIF1A

Abstract: Prolyl hydroxylase 3 (PHD3) is widely accepted as a tumor suppressor; however, the expression of PHD3 in various cancer types remains controversial. The present study aimed to investigate the association between PHD3 expression and the clinicopathological features of gastric cancer using reverse transcription‑quantitative polymerase chain reaction and immunohistochemistry. The effects of PHD3 in gastric cancer cell lines were assessed using western blot analysis and transwell migration assays. The present resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
(34 reference statements)
1
12
0
Order By: Relevance
“…Taken together, our observations and those by others highlight the role of PHD3 as a tumor suppressor [27,41,42,43]. Moreover, we show for the first time that PHD3 inhibition in cancer cells has profound effects on the tumor vasculature by influencing vessel morphology and the emergence of mural cells in a PDGF-C-dependent manner.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Taken together, our observations and those by others highlight the role of PHD3 as a tumor suppressor [27,41,42,43]. Moreover, we show for the first time that PHD3 inhibition in cancer cells has profound effects on the tumor vasculature by influencing vessel morphology and the emergence of mural cells in a PDGF-C-dependent manner.…”
Section: Discussionsupporting
confidence: 85%
“…In colorectal and gastric cancer as well as in glioma and astrocytoma PHD3 was also reported to function as a tumor suppressor [27,41,42,43]. In contrast, strongly tumor type-dependent effects on progression were reported for the related PHD2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…PHD3 knockdown in other cell lines (A549 and H1299 cells) enhanced pulmonary metastasis in a HIF-dependent manner that involved upregulation of TGFα, an EGFR ligand [140]. In gastric cancer, cell migration and invasion were significantly higher in PHD3-silenced tumor cells than controls, and both HIF1 and VEGF showed greater expression [141]. In mouse LM8 osteosarcoma, we showed that PHD3 is a tumor suppressor as silencing of this oxygen sensor led to enhanced tumor growth and dramatically changed vessel morphology that was directly related to significantly activated platelet-derived growth factor (PDGF)-C signaling in the vasculature of PHD3 knockdown tumors [142].…”
Section: The Phd-hif Axis As a Central Regulator Of Tumor Developmentmentioning
confidence: 96%
“…PHD3 knockdown in other cell lines (A549 and H1299 cells) enhanced pulmonary metastasis in a HIF-dependent manner that involved upregulation of TGFα, an EGFR ligand [37]. In gastric cancer, cell migration and invasion were significantly higher in PHD3-silenced tumor cells than controls, and both HIF-1 and VEGF showed greater expression [38]. In mouse LM8 osteosarcoma, we showed that PHD3 is a tumor suppressor as silencing of this oxygen sensor led to enhanced tumor growth and dramatically changed vessel morphology that was directly related to significantly activated platelet-derived growth factor (PDGF)-C signaling in the vasculature of PHD3 knockdown tumors [39].…”
Section: Phds As Central Regulators Of Tumor Developmentmentioning
confidence: 96%